2019
DOI: 10.1002/aenm.201902253
|View full text |Cite
|
Sign up to set email alerts
|

Emerging 2D Layered Materials for Perovskite Solar Cells

Abstract: Perovskite solar cells (PSCs) are now at the forefront of the state‐of‐the‐art photovoltaic technologies due to their high efficiency and low fabrication costs. To further realize the potential of this fascinating class of solar cells, nanostructured functional materials have been playing important roles. 2D layered materials have attracted a great deal of interest due to their fascinating properties and unique structure. Recently, the exploration of a wide range of novel 2D materials for use in PSCs has seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 192 publications
(302 reference statements)
0
77
0
Order By: Relevance
“…This method well modified the Pb 0 defects, and the resulting device retained 91% of the original stable PCE after MPP tracking for 500 h. [33] Recently, 2D perovskite capping layer as a surface passivation proved to be a good method to prevent ion migration and phase segregation in wide bandgap perovskites. [112][113][114][115][116] Huang group and Wolf group summarized the imperfections and their passivation in halide perovskite solar cells, respectively. [77,78] The passivation of perovskite materials proved to be an effective way to improve the photostability of PSCs.…”
Section: Ion Migration and Photogenerated Defectsmentioning
confidence: 99%
“…This method well modified the Pb 0 defects, and the resulting device retained 91% of the original stable PCE after MPP tracking for 500 h. [33] Recently, 2D perovskite capping layer as a surface passivation proved to be a good method to prevent ion migration and phase segregation in wide bandgap perovskites. [112][113][114][115][116] Huang group and Wolf group summarized the imperfections and their passivation in halide perovskite solar cells, respectively. [77,78] The passivation of perovskite materials proved to be an effective way to improve the photostability of PSCs.…”
Section: Ion Migration and Photogenerated Defectsmentioning
confidence: 99%
“…[22] Perovskites exhibit a comprehensive range of fascinating features including tunable color, a high absorption coefficient and long charge diffusion length. [3][4][5] Indeed, in early-2017, Bakr's group reported for the first time that perovskites show outstanding thermochromic properties. [29] The unusual crystallization behavior of halide perovskites plays an important role in their thermo-responsive behavior.…”
Section: Thermochromic Perovskites For Spwsmentioning
confidence: 99%
“…Despite this, several research groups in the PV field have paid further attention to the development of perovskite-based solar cells. [3][4][5] Researchers found that perovskite light absorbers exhibit promising photovoltaic properties, such as tunable bandgaps, high absorption coefficients, high charge carrier mobility, and long charge diffusion lengths. [6][7][8] In mid-2012, a collaborative publication by Grätzel and Park reported solid-state perovskite PV devices with a PCE of 9.7%.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of two-dimensional (2D) materials at different sections of perovskite solar cells (PSCs) represents an effective approach to enhance both the power conversion efficiency (PCE) and the lifetime stability of such photovoltaic technology. [1][2][3][4] Meanwhile, the exceptional optoelectronic properties of 2D materials and their compatibility with large-scale, solutionprocessable methods (e.g., roll-to-roll printing techniques) lay the ground for the direct integration of low-cost and flexible photovoltaic devices in emerging smart and multifunctional technologies. [5][6][7][8][9][10][11] The beneficial impact of graphene and related 2D materials in PSCs has been demonstrated both in mesoporous [12][13][14][15][16] and inverted planar structures, [17][18][19] as well as in their corresponding tandem systems.…”
Section: Introductionmentioning
confidence: 99%